Teacher professionalism in Greek primary schools - Athanasiadou, Despoina (2025)
This study examines teacher professionalism in Greek primary schools, focusing on how cultural, national, school, and personal contexts shape teachers’ perceptions and practices of professionalism. It aligns with contemporary research advocating for more nuanced approaches to professionalism (Day et al., 2023), moving beyond its historical association with qualifications, a specialised knowledge base, a service ethic, and autonomy (Furlong et al., 2000; Sachs, 2003). Employing an interpretive qualitative research design, this study explores the perspectives of 30 Greek primary school teachers from four schools through semi-structured interviews and thematic analysis. The findings reveal considerable variation in how Greek teachers understand and enact professionalism. This variation stemmed partly from teachers’ personal interpretations of professionalism and partly from external factors, including the role of school principals, the indirect influence of national policy, and broader Greek cultural values. This research extends the limited scholarship on teacher professionalism in Greek primary schools, offering deeper insights into how professionalism is both experienced and enacted in the Greek context. It also provides new evidence on how principals can influence the experience of professionalism, but they cannot dictate teachers’ professional perspectives or fully control their practices. Furthermore, this study contributes new evidence on autonomy as a component of teacher professionalism, highlighting its intricate relationship with agency and teacher identity. This study challenges decontextualised and dichotomous views of teacher professionalism, emphasising the need for more nuanced, context-sensitive approaches. At the same time, the diverse interpretations of professionalism expressed by the Greek teachers in this study raise critical questions about the standards of pupils’ education in Greek primary schools. This holds significant implications for policymakers, school leaders, and teachers, at a time when many European and OECD countries are making increasing efforts to enhance the quality of teaching pupils receive.